The distribution of talc within the Kevitsa Ni-Cu-PGE mine, Finland - McDonald, Isabel (Helsingin yliopisto, 2020)
Talc is a problematic alteration mineral at the Kevitsa Ni-Cu-(PGE) mine in Sodankylä, Finland, and its distribution and control were assessed in this thesis. Kevitsa is a polymetallic mine hosted in an ultramafic intrusion, extracting Ni, Cu, Co, Au, Pt and Pd, which are of increasing importance in green energy technologies. Talc – a common alteration product in ultramafic rocks – detrimentally interferes with the recovery of copper in the flotation stage of ore processing when concentrations exceed 5 wt. %, thus affecting the economics of mine operations. It was found different talc concentrations had different spatial associations and controls, with three dominant styles identified, and a multi-stage genesis of talc alteration is proposed. The talc styles identified in the study are as follows: (style 1) pervasive talc-chlorite alteration, (style 2) talc-dolomite alteration haloes proximal to dolomite veins and (style 3) talc on brittle structures, associated with magnetite. Low values of talc between 0.2-0.5 wt.% (style 1) were found to have no preferential spatial distribution, occurring as background alteration throughout the intrusion. Intermediate values (between 1-5 wt. %) were associated with late brittle fractures and structures (style 3), with a notable association with the NE-flt-rv1 fault zone. Style (2) was found to have a dominant structural control, specifically being associated with north-south trending structures. Dominant structures with this association identified are NS-flt1_flt-002 and NS-flt-2_flt-009. Highest values (commonly exceeding >10 wt. %) manifest themselves as alteration haloes proximal to veins, where talc-carbonate replaces the intercumulus mineral phases. Here it is proposed that ‘low talc’ alteration, style (1), was the first talc association to occur, generated by late magmatic fluids or regional metamorphism accompanying amphibole and serpentine alteration. The association observed as style (2) was likely generated by the infilling of north-south trending structures by ...